Synthesis of Nanocellulose Fibers from Lignocellulosic Biomass in Ionic Liquid: A Novel Approach - J.K. Prasannakumar; G.K. Prakash; B. Suresh; B.E. Basavarajappa; H.S. Onkarappa; Bharath K. Devendra; S.G. Prasannakumar (Recent Developments in Chemistry and Biochemistry Research Vol. 4, 2024)
The purpose of this study is to synthesize nanocellulose from ragi stalks, mango wood and groundnut husk and to compare their properties using an ionic liquid. As a developing nation, India has battled for decades to comply with global environmental and solid-waste management norms, which has been a significant obstacle. The two most significant natural sources of cellulose on Earth are wood and lignocellulosic crop biomasses. The most popular and extensively used biopolymer in the world after chemical treatment is cellulose, which has excellent toughness, affordability, biocompatibility, and thermal stability. In this study, nanocellulose was extracted from ragi stalk, mango wood and groundnut husk. The cellulose was alkali-treated with NaOH and bleached with sodium chlorite to remove lignin and hemicellulose. Ionic liquid (1- butyl-3-methylimidazolium chloride ([Bmim]Cl) solvent was used to treat the obtained cellulose. FTIR spectra highlight the functional groups and substantial conversion of cellulose to nanocellulose. The crystalline or semi-crystalline nature of synthesized nanocellulose was illustrated by XRD. The TEM images record the size of synthesized nanocellulose between 11.12 and 31.16 nm. The reduction in size is mainly due to ultrasonication and centrifugation. The thermal stability of the obtained nanocellulose was evidenced using TGA/DTA. The thermal studies insight that the synthesized nanocellulose samples possess superior degradation temperatures up to 473.8 ºC. This research seeks to demonstrate the remarkable practical applications of synthesized nanocellulose from agricultural biomass, which will undoubtedly meet India’s need for solid waste management and reduce chemical waste through a more realistic approach to nanocellulose manufacturing.